Synthesis and Characterization of Some Oxo and Dioxovandium(IV & V) Chelates with Thioamide Ligands - Pandey, R.N.; Shahi, Kalpana (Asian Journal of Chemistry, 2011)
Some oxo and dioxovanadium(IV & V) chelates of methyl, methoxy, ethoxy, hydroxyl and chloro derivatives of 1-substituted phenyl-tetrazoline-5-thione have been prepared and characterized by elemental analysis, molar conductivity, magnetic susceptibility measurements, IR, electronic and 1H NMR spectral studies. Tentative octahedral structure to dioxovanadium(V) and square pyramidal (C4V) structure to oxovanadium(IV) chelates is assigned.